Does the black middle class exist and are we members? : reflections from a research team - Khunou, Grace; Marsh, Kris; Chauke, Polite; Plank, Lesego; Igbanoi, Leo; Kgosiemang, Mabone (Bingley, U.K. : Emerald Publishing Limited, 2019)
Does the Black Middle Class Exist And Are We Members makes two contributions into the research of the Black Middle Class. First, it explores how Black South Africans conceptualize middle classness. Second, it demonstrates how this conceptualization informs researchers' social identity within the Black middle class.The book draws on historical social science literature for theoretical grounding and focuses on enriching theoretical perspectives on race and class from the perspective of the interviewee and the interviewer. It contextualizes both subjective and objective definitions of the term 'middle class' while highlighting it's constantly shifting perception.Does the Black Middle Class Exist And Are We Members reflects on the experience of the researchers interviews with Black middle class of South Africa. These reflections give a unique approach in understanding how researcher's subjectivism reflects the experiences of the South African Middle class.
Prelims -- Chapter 1: Who is The Black Middle Class in History and Theory? -- Chapter 2: The Black Middle Class: A Conceptual Moving Target? -- Chapter 3: Those Snobbish "Clever" Blacks: Preconceived Notions of The Black Middle Class -- Chapter 4: Thank You, But i Got This: Gender Dynamics Between Researchers and The Black Middle Class -- Chapter 5: What Do I Wear, and Do I Eat Their Food? Performing Middle Classness -- Chapter 6: Conclusion -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: Blacks -- South Africa; Middle class -- South Africa; Blacks -- Race identity -- South Africa; Social status -- South Africa; Social Science -- General; Society & social sciences